CuAgSe-based thermoelectric semiconductor crystal and preparation method thereof
Control the cooling gradient and movement rate through the Bridge Growth Method, prepare high -performance CUAGSE thermoelectric semiconductor crystals, solve the problems of complex synthesis, unruly products and small size in the existing technologies, and realize high -efficiency thermal electricity Performance and raw material utilization.
Patent Information
- Application Number
- CN202411963310.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, the synthesis of CuAgSe materials has problems such as complex processes and impure products, which leads to limited application in the field of thermoelectric semiconductors. The CuAgSe crystal material prepared by the floating zone method is small in size and low in raw material utilization.
Adopt the CUAGSE base heating semiconductor crystal with the Bridge Growth Legal system. By controlling the movement rate of cooling gradient and polycrystalline materials in the cooling gradient, a single CUAGSE crystal is obtained to significantly reduce the second phase content in the crystal, improve the raw materials in the crystal, increase raw materials Utilization rate.
The high -tech rate of CUAGSE base thermal electrical semiconductor crystals, the Sakawa Baker coefficient, the excellent thermoelectric performance and the utilization rate of the altitude, and solved the problem of low material size and low raw material utilization in existing technologies.
Smart Images

Figure CN119372786A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermoelectric semiconductor materials, and in particular to a CuAgSe-based thermoelectric semiconductor crystal and a preparation method thereof. Background Art
[0002] Thermoelectric materials are functional materials for heat-electric energy conversion, among which CuAgSe is a thermoelectric material with great potential. However, CuAgSe is difficult to synthesize, which leads to less research and application of CuAgSe. Currently, the synthesis of CuAgSe mainly includes melting method and chemical method. The chemical method includes electrochemical synthesis and template synthesis. However, the chemical method has the problems of complex process and impure product, which leads to the difficulty of effectively applying CuAgSe materials prepared by chemical method in the field of thermoelectric semiconductor. The melting method is simple and can be mass-produced, as shown in the literature Journal of Materials Chemistry A 2015, 3, 13662-13670.》 discloses a method for preparing CuAgSe-based thermoelectric semiconductor crystals, and another method for preparing a homogeneous bulk thermoelectric material by a one-step in-situ reaction disclosed in publication number CN105990511B; the above method uses Cu powder, Ag powder and Se powder to first press into blocks, and then pressurizes and sinters the blocks to form CuAgSe semiconductor crystal materials. This method has high density, uniform composition and can be mass-produced, but the CuAgSe crystal material obtained by hot pressing and sintering is small in size.
[0003] Therefore, in order to obtain a larger CuAgSe crystal material, the prior art uses a floating zone method to prepare CuAgSe crystal material, such as a CuAgSe material with a high preferential orientation and a preparation method and application thereof disclosed in Publication No. CN118317678A. This method can obtain a large-sized CuAgSe polycrystalline material with a higher single orientation. In addition, the method also points out that the crystal planes of the crystal material obtained by conventional melt annealing treatment are chaotic, and it cannot be guaranteed that the grown crystals can grow in layers, and it is impossible to obtain a larger-sized crystal material; while in the optical floating zone method, the second phase inside the crystal tends to melt in the liquid phase during the optical melting process, so that the second phase will be concentrated on the top of the polycrystalline material finally formed, and a crystal material with a high preferential phase can be obtained by removing the second phase. This also shows that the optical floating zone method has the problem of low raw material utilization. Summary of the invention
[0004] In order to overcome the problem of low raw material utilization rate caused by the generation of second phase during the melt growth of polycrystalline materials in the prior art, the present invention provides a CuAgSe-based thermoelectric semiconductor crystal and a preparation method thereof. The material is prepared by a Bridgman growth method. Compared with a CuAgSe-based thermoelectric semiconductor crystal prepared by a pressure sintering method, the material has high electrical conductivity, a slightly lower Seebeck coefficient, equivalent thermal conductivity, high thermoelectric figure of merit and high thermoelectric performance. The method can obtain CuAgSe crystals with high single orientation by controlling a temperature reduction gradient and a moving rate of the polycrystalline material in the temperature reduction gradient. The method can significantly reduce the content of the second phase in the crystal by controlling the temperature reduction gradient, can directly obtain CuAgSe crystals with high single orientation without the need to remove the second phase, and significantly improves the utilization rate of the CuAgSe polycrystalline raw material.
[0005] The specific technical scheme of the present invention is: A CuAgSe-based thermoelectric semiconductor crystal has a molecular formula of CuAgSe. The CuAgSe-based thermoelectric semiconductor crystal is made from single-element Cu, single-element Ag and single-element Se as raw materials through melting treatment and Bridgman growth method. The steps of the Bridgman growth method include high-temperature melting, gradient cooling growth and low-temperature insulation. The conditions of the gradient cooling growth are: the cooling gradient is 15-25°C / cm, and the movement rate of the polycrystalline material in the cooling gradient is 0.01-3 mm / h.
[0006] Preferably, the moving rate is 1.3-1.5 mm / h.
[0007] Preferably, the thermoelectric figure of merit of the CuAgSe-based thermoelectric semiconductor crystal is 0.5-0.7, and within the range of 300 K to 450 K, the average thermoelectric figure of merit is 0.4-0.6.
[0008] Preferably, the CuAgSe-based thermoelectric semiconductor crystal has a diameter of 10-80 mm and a length of 10-100 cm.
[0009] The invention provides a CuAgSe-based thermoelectric semiconductor crystal. The material is made of single-substance Cu, single-substance Ag and single-substance Se as raw materials through melt quenching and Bridgman growth method. The metal single substance can be directly processed without pre-processing the raw materials, and the process is simpler. The material is made by the Bridgman growth method. The CuAgSe-based thermoelectric semiconductor crystal obtained by the production has high single orientation, large grains and large size. Compared with the CuAgSe-based thermoelectric semiconductor crystal made by the pressure sintering method, the material has high electrical conductivity, slightly lower Seebeck coefficient, equivalent thermal conductivity, high thermoelectric figure of merit and high thermoelectric performance.
[0010] The present invention finds that when using the method disclosed in the prior art CN118317678A to grow CuAgSe crystals, more second phases will be produced during the crystal growth process using the optical floating zone method. These second phases will tend to dissolve in the melt. As the melt moves, the second phases will be continuously concentrated at the top of the crystal. Subsequently, only the top needs to be removed to obtain a single CuAgSe crystal with high orientation. The present invention finds that by controlling the descent rate, the appearance of the second phase can be suppressed, the content of the second phase in the crystal can be significantly reduced, and the CuAgSe-based thermoelectric semiconductor crystal can be used without removing the second phase, which can significantly improve the utilization rate of the CuAgSe polycrystalline raw materials.
[0011] A method for preparing the above-mentioned CuAgSe-based thermoelectric semiconductor crystal comprises the following steps: Step 1: Put single element Cu, single element Ag and single element Se into a crucible and seal it under vacuum, then melt the sealed crucible to make CuAgSe polycrystalline raw material; Step 2: Place the CuAgSe polycrystalline raw material in a crucible and seal it in vacuum, place the sealed crucible in a Bridgman growth device and perform high-temperature melting, gradient cooling growth and low-temperature insulation in sequence to produce a CuAgSe-based thermoelectric semiconductor crystal.
[0012] Preferably, the conditions for the melt treatment in step 1 include: a melt temperature of 950-1100°C and a heating rate of 2-10°C / min.
[0013] Preferably, the conditions for the melt treatment in step 1 also include: a swing time of 0.5 to 3 h, and a swing rate of 10 to 30 r / min.
[0014] Preferably, the heating rate of high temperature melting in step 2 is 1-2.5°C / min.
[0015] Preferably, in step 2, the bottom of the crucible is conical, with a taper of 17-54°, a crucible diameter of 10-80 mm, and a crucible length of 200-400 mm.
[0016] Preferably, the crucible is a double-layer crucible.
[0017] Preferably, the low temperature insulation temperature in step 2 is 550-500°C.
[0018] Compared with the prior art, this application has the following technical effects: (1) Compared with the CuAgSe-based thermoelectric semiconductor crystal made by pressure sintering, this material has high electrical conductivity, slightly lower Seebeck coefficient, comparable thermal conductivity, high thermoelectric figure of merit, and high thermoelectric performance; (2) This method can obtain CuAgSe crystals with high single orientation by controlling the cooling gradient and the movement rate of the polycrystalline material in the cooling gradient; (3) This method can significantly reduce the content of the second phase in the crystal by controlling the cooling gradient, and can directly obtain CuAgSe crystals with high single orientation without removing the second phase, thereby significantly improving the utilization rate of CuAgSe polycrystalline raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the X-ray diffraction pattern of the CuAgSe-based thermoelectric semiconductor crystal of Example 1.
[0020] Figure 2 Surface morphology and mapping of the CuAgSe-based thermoelectric semiconductor crystal of Example 1.
[0021] Figure 3 The conductivity line graphs of the CuAgSe-based thermoelectric semiconductor crystals of Example 1 and Comparative Example 1 in the range of 300K-450K are perpendicular to the axis and parallel to the axis. Example 1 is parallel to the axis and perpendicular to the axis, and Comparative Example 1 is Document 1.
[0022] Figure 4 It is a line graph of the Seebeck coefficient perpendicular to the axis and parallel to the axis of the CuAgSe-based thermoelectric semiconductor crystal of Example 1 and Comparative Example 1 in the range of 300K-450K. Example 1 is parallel to the axis and perpendicular to the axis, and Comparative Example 1 is Document 1.
[0023] Figure 5 It is a line graph of the thermal conductivity of the CuAgSe-based thermoelectric semiconductor crystals of Example 1 and Comparative Example 1 in the range of 300K-450K perpendicular to the axis and parallel to the axis. Example 1 is parallel to the axis and perpendicular to the axis, and Comparative Example 1 is Document 1.
[0024] Figure 6 It is a dimensionless figure of merit line graph of the CuAgSe-based thermoelectric semiconductor crystal in the range of 300K-450K of Example 1 and Comparative Example 1, Example 1 is parallel to the axial direction and perpendicular to the axial direction, and Comparative Example 1 is Document 1. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the embodiments.
[0026] Embodiment 1: A method for preparing a CuAgSe-based thermoelectric semiconductor crystal comprises the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1000 ° C, keep it warm for 1 hour, make the metal element in the crucible completely melt, then rock it at a rocking speed of 20 r / min for 1 hour, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0027] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 50 mm, a length of 200 mm, a conical bottom, and a taper of 30°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1000 ℃ (heating rate is 3 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 15 ℃ / cm). The quartz crucible moves slowly in the gradient cooling zone at a moving rate of 1.4 mm / h until all the melt is crystallized. Then, the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal with a length of 30 mm and a diameter of 50 mm. The low-temperature insulation time is 12 hours.
[0028] Embodiment 2: A method for preparing a CuAgSe-based thermoelectric semiconductor crystal comprises the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1000 ° C, keep it warm for 1 hour, make the metal element in the crucible completely melt, then rock it at a rocking speed of 20 r / min for 1 hour, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0029] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 50 mm, a length of 200 mm, a conical bottom, and a taper of 30°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1000 ℃ (heating rate is 3 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 15 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 1.3 mm / h until all the melt is crystallized. Then, the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal with a length of 30 mm and a diameter of 50 mm. The low-temperature insulation time is 12 hours.
[0030] Embodiment 3: A method for preparing a CuAgSe-based thermoelectric semiconductor crystal comprises the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1000 ° C, keep it warm for 1 hour, make the metal element in the crucible completely melt, then rock it at a rocking speed of 20 r / min for 1 hour, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0031] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 50 mm, a length of 200 mm, a conical bottom, and a taper of 30°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1000 ℃ (heating rate is 3 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 15 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 1.5 mm / h until all the melt is crystallized. Then, the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal with a length of 30 mm and a diameter of 50 mm. The low-temperature insulation time is 12 hours.
[0032] Embodiment 4: A method for preparing a CuAgSe-based thermoelectric semiconductor crystal comprises the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 950 ° C, keep it warm for 0.5 h, make the metal element in the crucible completely melt, then rock it at a rocking speed of 10 r / min for 0.5 h, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0033] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 10 mm, a length of 200 mm, a conical bottom, and a taper of 17°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 950 ℃ (heating rate is 2 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 15 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 0.01 mm / h until all the melt is crystallized. Then, the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal with a length of 10 mm and a diameter of 10 mm. The low-temperature insulation time is 12 hours.
[0034] Embodiment 5: A method for preparing a CuAgSe-based thermoelectric semiconductor crystal comprises the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1100 ° C, keep it warm for 3 h, make the metal element in the crucible completely melt, then rock it at a rocking speed of 30 r / min for 3 h, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0035] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 80 mm, a length of 400 mm, a conical bottom, and a taper of 54°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10-3 Pa, after 3 cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1100 ℃ (heating rate is 10 ℃ / min), the quartz crucible is kept in the melting zone for 12 h, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 25 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 3 mm / h until all the melt is crystallized. Then, the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 550 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal with a length of 80 mm and a diameter of 100 mm, and the low-temperature insulation time.
[0036] Comparative Example 1: Compared with Example 1, in Comparative Example 1, the pressure sintering method disclosed in Document 1: Journal of Materials Chemistry A2015, 3, 13662-13670 was used to prepare the CuAgSe-based thermoelectric semiconductor crystal, and the prepared CuAgSe-based thermoelectric semiconductor crystal had a diameter of 5 mm and a length of 5 mm.
[0037] Comparative Example 2: Compared with Example 1, in step 2 of Comparative Example 2, the quartz crucible is slowly moved in the gradient cooling zone at a too low moving rate of 0.2 mm / h, and comprises the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1000 ° C, keep it warm for 1 hour, make the metal element in the crucible completely melt, then rock it at a rocking speed of 20 r / min for 1 hour, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0038] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 50 mm, a length of 200 mm, a conical bottom, and a taper of 30°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1000 ℃ (heating rate is 3 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 15 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 0.2 mm / h until all the melt is crystallized, and then the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal, and the low-temperature insulation time is 12 hours.
[0039] Comparative Example 3: Compared with Example 1, in step 2 of Comparative Example 3, the quartz crucible is slowly moved in the gradient cooling zone at a too high moving rate, which is 3 mm / h, and comprises the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1000 ° C, keep it warm for 1 hour, make the metal element in the crucible completely melt, then rock it at a rocking speed of 20 r / min for 1 hour, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0040] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 50 mm, a length of 200 mm, a conical bottom, and a taper of 30°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1000 ℃ (heating rate is 3 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 15 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 3 mm / h until all the melt is crystallized. Then, the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal, and the low-temperature insulation time is 12 hours.
[0041] Comparative Example 4: Compared with Example 1, the crucible in step 2 of Comparative Example 4 is a single-layer crucible, and the other conditions are the same as those of Example 1.
[0042] Comparative Example 5: Compared with Example 1, the quartz crucible in step 2 in Comparative Example 5 is a flat-bottomed dry pan, and the other conditions are the same as those in Example 1.
[0043] Comparative Example 6: Compared with Example 1, the temperature of the melting zone in step 2 of Comparative Example 6 is too low, the temperature of the melting zone is 700° C., and the other conditions are the same as those in Example 1.
[0044] Comparative Example 7: Compared with Example 1, the temperature reduction gradient in the gradient cooling zone of step 2 in Comparative Example 7 is too small, and the temperature reduction gradient is 5°C / cm, which includes the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1000 ° C, keep it warm for 1 hour, make the metal element in the crucible completely melt, then rock it at a rocking speed of 20 r / min for 1 hour, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0045] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 50 mm, a length of 200 mm, a conical bottom, and a taper of 30°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1000 ℃ (heating rate is 3 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 5 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 1.4 mm / h until all the melt is crystallized, and then the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal, and the low-temperature insulation time is 12 hours.
[0046] Comparative Example 8: Compared with Example 1, the temperature reduction gradient in the gradient cooling zone of step 2 in Comparative Example 8 is too large, and the temperature reduction gradient is 40°C / cm, which includes the following steps: Step 1: weigh single element Cu, single element Ag and single element Se in a molar ratio of 1:1:1, the purity of single element Cu, single element Ag and single element Se is greater than 99.9%, put single element Cu, single element Ag and single element Se into a quartz crucible for vacuum sealing, put the sealed crucible into a rocking furnace, raise the temperature of the rocking furnace to 1000 ° C, keep it warm for 1 hour, make the metal element in the crucible completely melt, then rock it at a rocking speed of 20 r / min for 1 hour, make the raw materials fully mixed, and cool it to make CuAgSe polycrystalline raw material.
[0047] Step 2: Take 80 g of the above CuAgSe polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 50 mm, a length of 200 mm, a conical bottom, and a taper of 30°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 1000 ℃ (heating rate is 3 ℃ / min), the quartz crucible is kept in the melting zone for 12 hours, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the cooling gradient is 40 ℃ / cm). The quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 1.4 mm / h until all the melt is crystallized. Then, the quartz crucible is moved to the low-temperature zone (the temperature of the low-temperature zone is 500 ℃) for low-temperature insulation to form a CuAgSe-based thermoelectric semiconductor crystal, and the low-temperature insulation time is 12 hours.
[0048] Figure 1 is the X-ray diffraction pattern of the CuAgSe-based thermoelectric semiconductor crystal of Example 1, from Figure 1 It can be seen that the grown CuAgSe-based thermoelectric semiconductor crystal is a single phase.
[0049] Figure 2 The surface morphology and mapping of the CuAgSe-based thermoelectric semiconductor crystal of Example 1 are shown in FIG. Figure 2 It can be seen that the distribution of various elements in the CuAgSe-based thermoelectric semiconductor crystal is very uniform.
[0050] Figure 3 The conductivity line graph of the CuAgSe-based thermoelectric semiconductor crystals in Example 1 and Comparative Example 1 in the range of 300K-450K perpendicular to the axis and parallel to the axis is shown in FIG. Figure 3 It can be seen that in the range of 300-450K, the conductivity of the crystal perpendicular to the axis and parallel to the axis is higher than that of comparative example 1.
[0051] Figure 4The Seebeck coefficient line graph of the CuAgSe-based thermoelectric semiconductor crystals of Example 1 and Comparative Example 1 in the range of 300K-450K is perpendicular to the axis and parallel to the axis. Figure 4 It can be seen that in the range of 300-450K, the Seebeck coefficients of the crystal perpendicular to the axis and parallel to the axis are lower than those of comparative example 1.
[0052] Figure 5 The thermal conductivity of the CuAgSe-based thermoelectric semiconductor crystal in the range of 300K-450K perpendicular to the axis and parallel to the axis is shown in Figure 1. Figure 5 It can be seen that in the range of 300-450K, the thermal conductivity of the crystal perpendicular to the axis and parallel to the axis is comparable to that of Comparative Example 1.
[0053] Figure 6 is a line graph of dimensionless merit zT value of CuAgSe based thermoelectric semiconductor crystal in the range of 300K-450K for Example 1 and Comparative Example 1, from Figure 6 It can be seen that in the range of 300-450K, the dimensionless merit zT values of the crystal perpendicular to the axis and parallel to the axis are higher than those of comparative example 1.
[0054] Test example: The raw material utilization rates of the CuAgSe-based thermoelectric semiconductor crystals prepared in Examples 1 to 3, Comparative Examples 2 and 3 were calculated, and the second phase content in the prepared CuAgSe-based thermoelectric semiconductor crystals was tested and the raw material utilization rates were calculated. The second phase content is tested by X-ray diffraction pattern to calculate the raw material utilization rate. Raw material utilization rate = [(CuAgSe-based thermoelectric semiconductor crystal mass - second phase mass) / CuAgSe-based thermoelectric semiconductor crystal mass] × 100%. The test results are shown in Table 1.
[0055] Table 1 Test results
[0056] As shown in Table 1, the raw material utilization rates of Examples 1 to 3 are all above 99.95%, while the raw material utilization rates of Comparative Examples 2 and 3 are all less than 99%. The above results show that the moving rate has a significant effect on the content of the second phase in the grown CuAgSe-based thermoelectric semiconductor crystal. When the moving rate is between 1.2 and 1.5 mm / h, the content of the second phase can be guaranteed to be 0.0005% lower, ensuring that the CuAgSe-based thermoelectric semiconductor crystal can be used without the need for the second phase to be removed and processed. The results of Comparative Examples 2 and 3 show that too high and too low moving rates will result in the content of the second phase in the obtained CuAgSe-based thermoelectric semiconductor crystal being higher than 0.01%, and the CuAgSe-based thermoelectric semiconductor crystal with a second phase content higher than 0.01% needs to further remove the second phase before it can be used. In addition, inhibiting the generation of the second phase can also improve the raw material utilization rate of the CuAgSe polycrystalline raw material, and a larger size of CuAgSe-based thermoelectric semiconductor can be obtained at one time.
[0057] By analyzing the results of Example 1, Comparative Example 4 and Comparative Example 5, it was found that the crucible has a significant effect on the growth of CuAgSe-based thermoelectric semiconductor crystals. A single-layer crucible was used in Comparative Example 4, and the crucible in Comparative Example 4 broke during the melting stage, making subsequent solution growth impossible. A flat-bottomed crucible was used in Comparative Example 5, and it was found that the flat-bottomed crucible was prone to multiple crystal nuclei. During the subsequent crystal growth, too many crystal nuclei were oriented along multiple crystal nuclei at the same time, resulting in a reduction in the single orientation of the crystal.
[0058] By analyzing the results of Example 1 and Comparative Example 6, it was found that when the melting temperature of Comparative Example 6 was too low, the polycrystalline raw material could not be melted and subsequent crystal growth could not be performed.
[0059] By analyzing the results of Example 1, Comparative Example 7 and Comparative Example 8, it is found that the temperature reduction gradient also has a significant effect on the growth of CuAgSe-based thermoelectric semiconductor crystals. If the temperature reduction gradient is too small, the grains will be too small. If the temperature gradient is too large, it will affect the orientation of the crystal.
[0060] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A CuAgSe-based thermoelectric semiconductor crystal, characterized in that: The molecular formula is CuAgSe. The CuAgSe-based thermoelectric semiconductor crystal is made of single-element Cu, single-element Ag and single-element Se as raw materials through melting treatment and Bridgman growth method. The steps of the Bridgman growth method include high-temperature melting, gradient cooling growth and low-temperature insulation. The conditions of the gradient cooling growth are: the cooling gradient is 15-25 ℃ / cm, and the movement rate of the polycrystalline material in the cooling gradient is 0.01-3 mm / h.
2. The CuAgSe-based thermoelectric semiconductor crystal according to claim 1, characterized in that: The moving rate is 1.3-1.5 mm / h.
3. The CuAgSe-based thermoelectric semiconductor crystal according to claim 1, characterized in that: The thermoelectric figure of merit of the CuAgSe-based thermoelectric semiconductor crystal is 0.5-0.7; the average thermoelectric figure of merit of the CuAgSe-based thermoelectric semiconductor crystal in the range of 300 K to 450 K is 0.4-0.6; the diameter of the CuAgSe-based thermoelectric semiconductor crystal is 10-80 mm and the length is 10-100 mm.
4. A method for preparing a CuAgSe-based thermoelectric semiconductor crystal according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Put single element Cu, single element Ag and single element Se into a crucible and seal it under vacuum, then melt the sealed crucible to make CuAgSe polycrystalline raw material; Step 2: Place the CuAgSe polycrystalline raw material in a crucible and seal it in vacuum, place the sealed crucible in a Bridgman growth device and perform high-temperature melting, gradient cooling growth and low-temperature insulation in sequence to produce a CuAgSe-based thermoelectric semiconductor crystal.
5. The preparation method according to claim 4, characterized in that: The conditions for the melt treatment in step 1 include: a melt temperature of 950-1100°C and a heating rate of 2-10°C / min.
6. The preparation method according to claim 4, characterized in that: The conditions for the melt treatment in step 1 also include: a swing time of 0.5 to 3 h and a swing rate of 10 to 30 r / min.
7. The preparation method according to claim 4, characterized in that: The heating rate of the high temperature melting in step 2 is 1-2.5°C / min.
8. The preparation method according to claim 4, characterized in that: The bottom of the crucible in step 2 is conical, with a taper of 17-54°, a crucible diameter of 10-80 mm, and a crucible length of 20-40 cm.
9. The preparation method according to claim 8, characterized in that: The crucible is a double-layer crucible.
10. The preparation method according to claim 4, characterized in that: The temperature of the low temperature insulation in step 2 is 550~500℃.
Citation Information
Patent Citations
A method for preparing homogeneous bulk thermoelectric materials by one-step in-situ reaction
CN105990511B
Inorganic flexible and plastic semiconductor single crystal InSe material and preparation method and application thereof
CN113493924A
Ag2Se-based thermoelectric crystal material and preparation method thereof
CN115852471A
Preparation method of quaternary copper-based diamond-like semiconductor crystal
CN117385473A
High preferred orientation CuAgSe material and preparation method and application thereof
CN118317678A
Cited By
Preparation method of AgBiSe2-based semiconductor crystal
CN121853176A